Kurangnya Asupan Protein dan Zat Besi pada Remaja Putri di Daerah Manggarai, Nusa Tenggara Timur - Janggu, Jayanthi Petronela; Manggul, Makrina Sedista; Nanur, Fransiska Nova; Trisnawati, Reineldis (FORIKES, 2024)
Anemia is a global health problem that is often experienced by young women, one of the causes of which is inadequate nutritional intake, especially protein and iron. The aim of this study was to determine the average and proportion of protein and iron intake in adolescent girls. This research applied descriptive methods to 83 adolescent girls aged 13-14 years who were selected using purposive sampling techniques. Measurement of nutritional intake was carried out using the estimated food record sheet. Once collected, the data was analyzed descriptively in the form of means and percentages of each intake. The results of the study showed that the average protein intake only met 67%, namely 40.4 grams/day and the average iron intake only met 28%, namely 4.3 mg/day. It was concluded that the protein and iron intake of adolescent girls was below the nutritional adequacy standard and there was a failure to obtain protein and iron due to eating habits which resulted in a lack of portions and variety of food consumed.Keywords: adolescent girls; anemia; protein intake; iron intake ABSTRAK Anemia adalah masalah kesehatan global yang sering dialami oleh remaja putri, yang salah satu penyebabnya adalah asupan gizi yang tidak memadai terutama protein dan zat besi. Tujuan dari penelitian ini adalah untuk mengetahui rerata dan proporsi asupan protein dan zat besi pada remaja putri. Penelitian ini menerapkan metode deskriptif yang dilakukan pada 83 remaja putri berusia 13-14 tahun yang dipilih dengan teknik purposive sampling. Pengukuran asupan nutrisi dilakukan menggunakan lembar estimated food record. Setelah terkumpul, data dianalisis secara deskriptif berupa rerata dan persentase dari masing-masing asupan. Hasil penelitian menunjukkan bahwa rerata asupan protein hanya memenuhi 67% yaitu sebesar 40,4 gram/hari dan rerata asupan zat besi hanya memenuhi 28% yaitu sebesar 4,3 mg/hari. Disimpulkan bahwa asupan protein dan zat besi remaja putri berada di bawah standar angka kecukupan gizi dan adanya kegagalan mendapatkan protein dan zat besi akibat kebiasaan makan yang berdampak pada kurangnya porsi dan ragam makanan yang dikonsumsi.Kata kunci: remaja putri; anemia; asupan protein; asupan zat besi